Performance of a New Aeronautic Oil-Guiding Splash Lubrication System - Yu Dai; Xi Chen; Duan Yang; Lanjin Xu; Xiang Zhu (Lubricants, 2022)
Among ever-increasing demands for low power consumption, low weight, and compact reducer systems, an oil-guiding splash lubrication method integrating the oil-guiding cylinder and pipes is suggested to be more suitable for light helicopters, instead of conventional splash or oil jet lubrication. Aiming at improving the lubrication and cooling performance of this special lubrication method, this paper introduces an oil-guiding channel to increase oil quantity reaching the driving gear, bearings, and spline. Firstly, the lubrication and cooling effect of the oil-guiding channel in the main gearbox is investigated at various speeds and oil depths by leveraging with a computational fluid dynamics (CFD) technique. Then, a specialized test bench is set up and utilized for experiments to verify the CFD study. These results show that the numerical results are very satisfactory with the data of experimentation, and the maximum value of relative errors is no more than 15%. What is more, the oil flow rate passing through the monitoring plane with the oil-guiding channel is much greater than that without the channel by about three orders of magnitude. It also suggests that the oil-guiding channel could dramatically increase the lubricating oil in the meshing gear pair, and significantly improve the lubrication and cooling effect.